Transcriptomics and Proteomics Analyses of the Responses of Propionibacterium acidipropionici to Metabolic and Evolutionary Manipulation - Liu, Tingting; Zhao, Qianru; Li, Yang; Zhu, Liying; Jiang, Ling; Huang, He (Frontiers in Microbiology, 2020)
We first performed a combination of metabolic engineering (deletion of ldh and poxB and overexpression of mmc) with evolutionary engineering (selection under oxygen stress, acid stress and osmotic stress) in Propionibacterium acidipropionici. The results indicated that the mutants had superior physiological activity, especially the mutant III obtained from P. acidipropionici-Δldh-ΔpoxB+mmc by evolutionary engineering, with 1.5-3.5 times higher growth rates, as well as a 37.1% increase of propionic acid (PA) titer and a 37.8% increase PA productivity compared to the wild type. Moreover, the integrative transcriptomics and proteomics analyses revealed that the differentially expressed genes (DEGs) and proteins (DEPs) in the mutant III were involved in energy metabolism, including the glycolysis pathway and tricarboxylic acid cycle (TCA cycle). These genes were up-regulated to supply increased amounts of energy and precursors for PA synthesis compared to the wild type. In addition, the down-regulation of fatty acid biosynthesis and fatty acid metabolism may indicate that the repressed metabolic flux was related to the production of PA. Quantitative reverse-transcription polymerase chain reaction (qRT-PCR) was performed to verify the differential expression levels of 16 selected key genes. The results offer deep insights into the mechanism of high PA production, which provides the theoretical foundation for the construction of advanced microbial cell factories.